Pathophysiology and potential future therapeutic targets using preclinical models of COVID-19. Issue 4 (7th December 2020) - Kumar, Rahul; Lee, Michael H.; Mickael, Claudia; Kassa, Biruk; Pasha, Qadar; Tuder, Rubin; Graham, Brian
Severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) gains entry into the lung epithelial cells by binding to the surface protein angiotensin-converting enzyme 2. Severe SARS-CoV-2 infection, also known as coronavirus disease 2019 (COVID-19), can lead to death due to acute respiratory distress syndrome mediated by inflammatory immune cells and cytokines. In this review, we discuss the molecular and biochemical bases of the interaction between SARS-CoV-2 and human cells, and in doing so we highlight knowledge gaps currently precluding development of new effective therapies. In particular, discovery of novel treatment targets in COVID-19 will start from understanding pathologic changes based on a large number of autopsy lung tissue samples. Pathogenetic roles of potential molecular targets identified in human lung tissues must be validated in established animal models. Overall, this stepwise approach will enable appropriate selection of candidate therapeutic modalities targeting SARS-CoV2 and the host inflammatory response. A large number of autopsy samples and reliable preclinical animal models are required to understand the inflammatory process in #COVID19 https://bit.ly/3jWUVp4